2016
DOI: 10.1590/s0100-204x2016000100003
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de macieiras 'Imperial Gala' e 'Mishima Fuji' em diferentes porta-enxertos

Abstract: Resumo -O objetivo deste trabalho foi avaliar a influência de diferentes porta-enxertos no desempenho das cultivares de macieira (Malus domestica) Imperial Gala e Mishima Fuji. O delineamento experimental utilizado foi o de blocos ao acaso, com quatro repetições. Performance of 'Imperial Gala' and 'Mishima Fuji' apples on different rootstocksAbstract -The objective of this work was to evaluate rootstock effect on the performance of the Imperial Gala and Mishima Fuji apple (Malus domestica) cultivars. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 17 publications
(10 reference statements)
1
19
0
5
Order By: Relevance
“…For low fertility soils, regardless of the cultivar, rootstock CG.210 is the most indicated. Pasa et al (2016) observed that, among six rootstocks of the Geneva series evaluated, four showed performance similar to M.9/Marubakaido (interstem) for the soil and climate conditions of São Joaquim region, which can be an advantage, since the rootstocks do not present regrowth problems, not requiring additional labor force for theirs control.…”
Section: Introductionmentioning
confidence: 91%
“…For low fertility soils, regardless of the cultivar, rootstock CG.210 is the most indicated. Pasa et al (2016) observed that, among six rootstocks of the Geneva series evaluated, four showed performance similar to M.9/Marubakaido (interstem) for the soil and climate conditions of São Joaquim region, which can be an advantage, since the rootstocks do not present regrowth problems, not requiring additional labor force for theirs control.…”
Section: Introductionmentioning
confidence: 91%
“…Rootstock 'G. 814' is developed by the breeding program of CornellGeneva (Geneva ® series), that state the most complete rootstocks in relation to high-density systems and resistant to major pests and soil diseases of apple orchards in Brazil (DENARDI et al, 2015), and according to PASA et al (2016), the rootstock from this series looks very promising for the South region of Brazil. Thus, the micropropagation of adapted rootstocks to different apple cultivars is being widely studied today in order to obtain a commercial scale production and the possible replacement by new rootstocks, which requires the availability of large amount of propagation material.…”
Section: Thementioning
confidence: 99%
“…Rootstocks G.202 and G.213 are categorized as dwarfing, equivalently to M.9, but the G.213 is one of the most adapted and stable bearing in southern Brazilian conditions, whereas the rootstock G.202 presented less yield constancy throughout years of experimentation compared to traditional Marubakaido/M.9 interstock rootstock (DENARDI et al, 2015). Rootstock G.814 presents intermediate vigor compared to Marubakaido/M.9 interstock, which is considered semi-vigorous, and both are equivalent in yield of 'Imperial Gala' besides presenting the potential for use in high density orchards (PASA et al, 2016).…”
Section: Introductionmentioning
confidence: 96%